The Impact of Spray Cryotherapy on Lesion-Induced Osteitis in a New Murine Experimental Model - Ioana Maria Porfire (Irimia); Alexandru Flaviu Tabaran; Madalina Luciana Gherman; Veronica Elena Trombitas; Silviu Albu (Medicina, 2023)
Background and Objectives: Endoscopic sinus surgery is considered the gold management strategy for difficult-to-treat chronic rhinosinusitis. The inflammatory bony process is incriminated as being involved in the unfavorable evolution and recurrence of the disease. Osteitis is significantly increased in patients that have been previously submitted to surgery, and it is more often present in patients with extended radiological disease and in patients undergoing revision surgery. The aim of the research is to demonstrate the presence of inflammations and neo-osteogenesis associated with nasal mucosal surgical injury and the correlation between their severity and to evaluate the efficacy of low-pressure spray cryotherapy in reducing inflammation and bone remodeling. Materials and Methods: The experimental murine model was conducted over a period of 80 days and included a total of 60 adult female Wistar rats, with three periods of withdrawal of 20 individuals each from the experiment. After inducing a bilateral mechanical injury by brushing, low-pressure spray cryotherapy application was performed unilaterally, and tissue samples were prepared specifically for histological analysis. The scores for inflammation and osteitis were compared over time and between the two nasal fossae. Results: Osteitis and inflammation were induced by a simple mucosal brushing lesion, similar to surgical injury. We identified the presence of inflammation in 95% of the specimens, and it was present over time. Moreover, criteria for bone remodeling were clearly highlighted in a percentage of 72% of the specimens. There was a direct correlation between the severity of inflammation and neo-osteogenesis, with a statistical significance of p = 0.050. Low-pressure spray cryotherapy was safe and effective in reducing inflammation (p = 0.020) and osteitis (p = 0.000) with a safety profile. Conclusions: Low-pressure cryotherapy reduces the severity of mucosal inflammation and osteitis in lesion-induced neo-osteogenesis.